The physico-chemical properties of ті-containing stainless steel composites and its photoactivity - O. V. Sanzhak; D. V. Brazhnyk; V. V. Honcharov; V. A. Zazhigalov; F. A. Azimov (Хімія, фізика та технологія поверхні)
The present study aims to obtain the supported Ti-containing catalyst on a surface of stainless steel foil by low temperature ionic implantation method. The geometrical sizes of the implantation chamber allow one to synthesize composites with the maximum size of 30?30 cm. The shape and size of the catalysts provide an opportunity to use obtained samples for removal of harmful substances from both aqueous solutions and gas mixtures. A quantitative estimation of bond strength of the surface layer of the prepared composites was realized by the use of sclerometric method. It is shown that implantation of titanium ions on stainless steel foil provide significant increase in surface layer mechanical strength. The heat treatment of the sample leads to a decrease in this strength, but its value rests higher than that in initial support (stainless steel). The composition of samples surface and the effect of calcination temperature were determined by XRD, SAXS, SEM, AFM, and XPS. It is shown that after ionic implantation nanoscale layer of the implant on the surface of stainless steel was formed. Presence of titanium oxide, nitride and oxynitride was determined by XPS method. The high photocatalytic activity of this catalyst in the process of neutralizing benzene in aqueous solutions under irradiation with visible light, which significantly exceeds its activity under UV-radiation was shown. Increasing the calcination temperature leads to decreasing the samples activity and can be explained by the influence of the ratio between the nitride, oxynitride, and oxide phases of titanium. Exactly the presence of those phases on the surface explains its high activity in the degradation of benzene in aqueous solution under visible light irradiation. Thus, using of the obtained samples in the neutralization of aqueous benzene solutions under visible light irradiation is perspective from ecological point of view.